Paysages, mobilisations citoyennes et acceptabilité sociale de projets éoliens terrestres - Philippe Hamman (VertigO, 2022)
This paper brings the virtuous calls to energy transition and its technical equipment in confrontation with its actual implementation through local renewable energy projects, by studying the case of onshore wind energy projects from a Franco-German comparative perspective. The analysis rests on a comparative review of the recent French-, German- and English-language literature in the social sciences in order to approach and frame the main issues, both on a theoretical and more practical level, related to conflict and participation among key players, scales of action, or the multiple socio-economic, environmental or aesthetic and sensory perceptions of wind energy. The aim is to identify fruitful approaches for the analysis of the “new landscapes” of wind energy, based on analysis of the controversies around citizen participation/mobilization and social acceptability, while taking into account the insights of research on energy transition / Wende at the local scale in both French and German territories. Analysis of the research on the subject has been conducted from a qualitative, not bibliometric, perspective; it has not sought exhaustiveness and is based on scholarly publications rather than on grey literature or practitioner sources; it has also tried to maintain a balance between French and German studies and to select easily accessible material, published papers or books, rather than PhD dissertations; finally, to provide concrete illustrations, the analysis has mainly focused on the border areas of the Upper Rhine region, without limiting itself to them.